Eugenol significantly affects the flow of its nanodroplet gel - Pramod, Kannissery; Shanavas, Salim; Ansari, Shahid H.; Ali, Javed (International Journal of Pharmaceutical Investigation)
Introduction: Development of novel biomaterials for drug delivery which forms a part of the so called novel drug delivery systems has always been exhilarating. Mechanical evaluation of polymer based topical gels, which would be subjected to load or stress during its application, is inevitable. Methods: Rheological characterization was done by studying viscosity and yielding. Rheological modeling was also carried out. Results: The viscosity and yield stress were inversely dependent on the eugenol concentration. The gels followed Herschel–Bulkley and Bingham rheological models. Conclusion: Nanodroplets are colloidal systems and the microstructural changes in the Carbopol based nanodroplet gels were unveiled using rheometry.
Keywords: Flow curve; microstructure; nanodroplet; rheological model